Self-Medication Practices in Pokhara: A Study of Knowledge and Purpose among Non-Medical Students - Subedi, Chudamani (Prithvi Journal of Research and Innovation, 2021)
This study has tried to assess the self-medication practice among non-medical students. For this purpose, data were collected from 206 Bachelor’s and Master’s level students by using self-administered questionnaire at Prithvi Narayan Campus, Pokhara. Quick relief from pain is one of the reasons for self-medication, followed by previous experiences of illness, pharmacist’s advice, ease and convenience and time saving. The majority of students has been practiced self-medication to treat headache (62.9%), fever (32.7%), gastric acidity (23.9%), cough (27.3%), common cold (34%), dental pain (18.5%) and dandruff (24.4%). Almost two fifth of the respondents (37.37%) had knowledge regarding the composition of drugs and minority (8.74%) that had knowledge about dose, content, therapy duration and reaction of the drug. In addition, the majority of the respondents practiced Antipyretic (38.6%) followed by analgesics (33.4%), general antibiotics (17.7%) and anti-ulcerants (14.1%) without proper consultation with professionals. The findings of the study showed that non-medical students had self-medication practices, depending on their age, gender and academic level. Due to a high level of practice on self-medication, the study recommended that the concerned authority should formulate a set of rules and implement to prevent such practices in the university, providing adequate facilities for healthcare medical treatment.